KETAHANAN PANGAN RUMAH TANGGA NELAYAN DI DESA SUKAJAYA LEMPASING KECAMATAN TELUK PANDAN KABUPATEN PESAWARAN - Delly, Defline Putri; Prasmatiwi, Fembriarti Erry; Prayitno, Rio Tedi (Lampung University, 2020)
The aims of this research are to analyze the level of food security, the factors that affect the level of food security, and the efforts to increase the level of food security of fisherman household. The location of this research is chosen purposively in Sukajaya Lempasing Village, Teluk Pandan Subdistrict, Pesawaran Regency in which respondents are 51 fisherman households. The data of this research are primary data and secondary data,collected in February ? May2018 and analyzed by cross-classification between the share of food expenditure and availability in addition to food sufficiency level, ordinal logistic regression, and descriptive qualitative analysis. The results of the research showed thatthe majority of respondent classified as less food were68.63% of respondents.The rest respondents were classified as foods secure13.73%, vulnerable to food 5.88%, and food insecure11.76%. The affecting factors on the level of food security were formal education level of housewives and household food expenditure. The efforts to increase the level of food security by Government were through monitoring food availability and food reserves, developing food distribution and stabilize food prices, Program Keluarga Harapan (PKH), and Raskin.While the efforts by fisherman household themselves werefood loan (92.16%) andchanging dietary habit(7.84%). Keywords: cross-classification, fisherman household, food security